Medical students' understanding of the concept of a soul. Issue 6 (3rd May 2013) - Martyn, Helen; Barrett, Anthony; Nicholson, Helen D.
<x xml:space="preserve">Abstract</x> The concept of a soul has been discussed throughout religious, philosophical, and scientific circles, yet no definitive description exists. Recent interviews with medical students during the production of a documentary film identified that many believed in the concept of a soul. This study explores students' understanding of the concept of a soul. The 2011 cohort of second‐year medical students at the University of Otago in Dunedin, New Zealand were invited to participate in an online survey with a free text response asking students to describe their understanding of the soul. The descriptions of the soul included the soul as a "spirit" or "life force" and some described the soul as giving a person their "values" and "personality." Students discussed the location of a soul with most stating that the soul was not attached to the body, but others mentioned the heart or the brain as the seat of the soul. A common theme related to the mortality of the soul emerged, with most believing that the soul left the body at death. Some students' concept of a soul was related to their religious beliefs, while others who did not believe in the concept of a soul described it as a "myth" used to bring comfort at the time of death. Medical students have varied opinions on the concept and importance of the soul. It is important to recognize the diversity of views when exploring the process of death and spirituality with medical students. Anat Sci Educ 6: 410–414. © 2013 American Association of Anatomists.